SISTEM RESIRKULASI AIR TERKENDALI PADA PEMBENIHAN IKAN PATIN (Pangasius hypophthalmus) - Umi Hanifah; Budi Indra Setiawan (Jurnal Keteknikan Pertanian, 2007)
ABSTRACT This research was conducted to design a controlled fish hatchery system. This research dealt win 1) Designs of water recirculation and filtration system, 2) Water level control system, and 3) Tests of recirculation end filtration system for fish hatchery. Recirculation system was built in an insulated room with dimension of 6 x 4 x 3 m, used six aquariums, a sedimentation tank, a filtration unit, a water supply tank, a submersible pump and pipe with 1.25 cm in diameter. Multilayer horizontal filtration unit was used. The system consisted of mechanical filter layer, biological filter layer, and chemical filter layer. On-off controller was designed to control the pump. Pressure sensor model HTVN-100KP was used to detect the water level. The water level controller could control filtration process successfully. This water recirculation system was appropriated for practical uses. This system could decrease water use and saved energy considerably. Diterima: 16 Mei 2007, Disetujui: 18 Mei 2007